1998
DOI: 10.1016/s0022-5223(98)00444-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of development of antibodies to hla and cytomegalovirus mismatch on lung transplantation survival and development of bronchiolitis obliterans syndrome

Abstract: These data suggest that bronchiolitis obliterans syndrome is the result of an immune-mediated process in which HLA antibodies and cytomegalovirus may play a significant role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(94 citation statements)
references
References 19 publications
4
88
1
1
Order By: Relevance
“…Previous studies suggested a role for HLA antibodies after lung transplantation. [5][6][7][8]22,23 Girnita et al found that HLA antibodies are associated with increased frequency and more severe acute rejections after lung transplant, 5 as well as increased incidence of BOS. 6 Their studies had small patient cohorts and, although they used solid-phase antibody assays for HLA antibody detection, they were enzyme-linked immunoassay (ELISA)-based and, as such, probably underestimated the level of HLA antibody production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested a role for HLA antibodies after lung transplantation. [5][6][7][8]22,23 Girnita et al found that HLA antibodies are associated with increased frequency and more severe acute rejections after lung transplant, 5 as well as increased incidence of BOS. 6 Their studies had small patient cohorts and, although they used solid-phase antibody assays for HLA antibody detection, they were enzyme-linked immunoassay (ELISA)-based and, as such, probably underestimated the level of HLA antibody production.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested an association between HLA antibodies detected post-transplant and acute rejection and BOS. [5][6][7][8] Girnita et al showed an association between development of HLA antibodies and acute rejection 5 and BOS 6 in a small series of lung transplants. However, their analysis was not time-dependent and did not account for time to BOS.…”
mentioning
confidence: 99%
“…Both direct and indirect effects are often present simultaneously, and the relative clinical contributions of any of these mechanisms are uncertain. In general, CMV seropositivity and receipt of seropositive organs and viremia are linked in many, but not all, studies to diminished long-term graft function (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Furthermore, most studies have indicated that successful antiviral prophylaxis has a beneficial effect on long-term graft function (8).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in in vitro models, CMV upregulated the expression of IL-8 in fibroblasts; this major mediator of the inflammatory response may play a role in the pathogenesis of bronchiolitis (23). patients (D À /R À ) (10,33,34,45,46 (47). A recent study from the Swiss Transplant Cohort Study (STCS), however, suggested that despite the use of universal antiviral preventive strategies, CMV-seropositive status remained associated with higher rates of biopsy-proven acute rejection compared with D À /R À patients (33).…”
Section: Viral Infections and Chronic Allograft Dysfunctionmentioning
confidence: 99%